2006
DOI: 10.1007/s00268-006-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Neoadjuvant Therapy Compared with Surgery Alone for Resectable Esophageal Cancer in a Population‐based Study

Abstract: Surgical outcomes with and without neoadjuvant therapy were equivalent. Only patients with a complete histopathological response after neoadjuvant treatment had better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…nCRT has been shown to give more tumour regression, increase R0 resection rates and reduce the risk of lymph node metastasis, but none of these trials showed any statistically significant benefit regarding survival. Patients who respond to treatment with complete histological response have increased survival compared with non‐responders.…”
Section: Introductionmentioning
confidence: 99%
“…nCRT has been shown to give more tumour regression, increase R0 resection rates and reduce the risk of lymph node metastasis, but none of these trials showed any statistically significant benefit regarding survival. Patients who respond to treatment with complete histological response have increased survival compared with non‐responders.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the implementation of preoperative CRT was extensive and fast, which could probably be explained by the usage of embedded logistics within the framework of the Dutch CROSS trial as radiotherapy institutes in the Netherlands are mostly independent from hospitals and patients need to be referred. Even though the implementation of preoperative CRT was early and possibly premature in the Netherlands, it seems that the extensive administration of preoperative CRT was even earlier in Sweden [17].…”
Section: Multimodality Treatment Trendsmentioning
confidence: 99%
“…Since the time of initiating the reorganisation of cancer services, survival of patients undergoing curative surgery has improved from 34% for oesophageal tumours and 40% for gastric tumours to 45% and 50%, respectively [16,17]. Whilst these improvements can not directly be related to the reorganization of services, it is plausible that the concentration of curative surgery brought about improvements in survival in this group of patients.…”
Section: Resultsmentioning
confidence: 99%